Combining embedded mean-field theory with linear-scaling density-functional theory - Prentice, JCA; Charlton, RJ; Mostofi, AA; Haynes, PD (American Chemical Society, 2019)
We demonstrate the capability of embedded mean-field theory (EMFT) within the linear-scaling density-functional-theory code ONETEP, which enables DFT-in-DFT quantum embedding calculations on systems containing thousands of atoms at a fraction of the cost of a full calculation. We perform simulations on a wide range of systems from molecules to complex nanostructures to demonstrate the performance of our implementation with respect to accuracy and efficiency. This work paves the way for the application of this class of quantum embedding method to large-scale systems that are beyond the reach of existing implementations.